Real-Time Wearable Cervical Posture Monitoring in Dentistry: A Prospective Usability Trial with Dental Students - Qutieshat, Abubaker; Al-Busaidi, Ritaj; Al-Ghammari, Samiya; Koofan, Al-Wejdan; Al-Lawati, Tuqa; Alrashdan, Mohammad S.; Petropoulou, Polyxeni (European Journal of Dentistry, 2025)
Dentists routinely adopt forward-lean postures that can lead to chronic spinal musculoskeletal disorders. Wearable real-time feedback may prompt microadjustments that preserve spinal health. This article aims to develop a wearable device for real-time detection of forwardleaning posture in dentistry, to assess its usability and alert rate during standardized student tasks, and to estimate cervical-disc fatigue lifetime from the measured headflexion profile using a simplified S-N model.An assistive device was constructed around an Arduino Uno interfaced with a three-axis FC-51 tilt-switch module, calibrated to trigger at > 30 degrees of head flexion. A piezo buzzer emitted pulsatile alerts when tilt exceeded the threshold. Twenty-four dental students (12 fourth year, 12 fifth year) wore the device during 30-minute simulated operative sessions. A research assistant logged each alert in real time. Postsession questionnaires (5-point Likert scale) assessed comfort, intrusiveness, distraction, workflow impact, and posture awareness. Qualitative feedback on power, alert modalities, and design refinements was collected. A fatigue model based on an S-N curve framework used measured angles to estimate years to cervical-disc fatigue under typical clinical exposure.Head flexion averaged 42.7 degrees (standard deviation 9.4). The device generated a mean of 7.9 alerts per session, with no significant difference between year levels. Likert ratings indicated high comfort, low intrusiveness and distraction, minimal workflow disruption, and enhanced posture awareness; 79% of participants expressed willingness to adopt the device. Common suggestions included rechargeable power, multimodal alerts, slimmer enclosures, and customizable thresholds. The S-N fatigue model predicted disc fatigue onset at approximately 20.6 years for pure flexion and 16.0 years when lateral tilt was also considered, aligning with clinical data from the literature. Simulated use of the device, limiting “bad posture” to 1 minute per day, extended the model's fatigue lifetime to over 900 years.The goggle-mounted tilt-sensor device effectively detected and interrupted excessive forward-lean postures, was well accepted by users, and provided insights for ergonomic design improvements. Coupled with an S-N fatigue model, this approach offers both a practical intervention and a quantitative framework for mitigating career-long spinal risk in dentistry. Future work should validate long-term musculoskeletal outcomes and explore integration into clinical training.
Keywords: ergonomics; intervertebral disc; musculoskeletal pain; posture; wearable technology